2017
DOI: 10.1016/j.molcel.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Repair of UV-Induced DNA Damage Independent of Nucleotide Excision Repair Is Masked by MUTYH

Abstract: DNA lesions caused by UV damage are thought to be repaired solely by the nucleotide excision repair (NER) pathway in human cells. Patients carrying mutations within genes functioning in this pathway display a range of pathologies, including an increased susceptibility to cancer, premature aging, and neurological defects. There are currently no curative therapies available. Here we performed a high-throughput chemical screen for agents that could alleviate the cellular sensitivity of NER-deficient cells to UV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…To gain insights into how TM-induced DNA damage is sensed and repaired in host cells, we next asked whether mutation of genes encoding key repair factors would render cells hypersensitive to TM. Inactivating mutations were generated in the human haploid cell line HAP1 (32, 33). Equal numbers of cells for each mutant line were cultured with increasing concentrations of TM, TV, or controls, and cell viability was measured (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into how TM-induced DNA damage is sensed and repaired in host cells, we next asked whether mutation of genes encoding key repair factors would render cells hypersensitive to TM. Inactivating mutations were generated in the human haploid cell line HAP1 (32, 33). Equal numbers of cells for each mutant line were cultured with increasing concentrations of TM, TV, or controls, and cell viability was measured (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…UV‐induced DNA lesions have been thought to be repaired solely by NER. However, a recent study demonstrated the existence of an NER‐independent repair mechanism for removing UV‐induced DNA damage in human cells (116). An antidiabetic drug, acetohexamide, was recently identified as an agent that alleviates the UV sensitivity of NER‐deficient cells.…”
Section: Updated Models Of Uv‐induced Dna Damage Responsesmentioning
confidence: 99%
“…Chemical screens have been used for decades to assess the toxicity of drugs, and the development of high-throughput readouts now allow for the analysis of bigger libraries comprising hundreds to thousands of compounds [197,198]. For instance, screening of a chemical library allowed the identification of a potent inhibitor of a mutated form of isocitrate dehydrogenase 2 (IDH2), which is expressed in acute myelogenous leukemia, and which is now used as a chemotherapeutic [199].…”
Section: Outlook: Approaches To Identify Interactions Between Metabolmentioning
confidence: 99%